Simultaneous Liver–Kidney Allocation Policy: A Proposal to Optimize Appropriate Utilization of Scarce Resources. Issue 3 (30th January 2016) - Formica, R. N.; Aeder, M.; Boyle, G.; Kucheryavaya, A.; Stewart, D.; Hirose, R.; Mulligan, D.
Abstract : The introduction of the Mayo End‐Stage Liver Disease score into the Organ Procurement and Transplantation Network (OPTN) deceased donor liver allocation policy in 2002 has led to a significant increase in the number of simultaneous liver–kidney transplants in the United States. Despite multiple attempts, clinical science has not been able to reliably predict which liver candidates with renal insufficiency will recover renal function or need a concurrent kidney transplant. The problem facing the transplant community is that currently there are almost no medical criteria for candidacy for simultaneous liver–kidney allocation in the United States, and this lack of standardized rules and medical eligibility criteria for kidney allocation with a liver is counter to OPTN's Final Rule. Moreover, almost 50% of simultaneous liver–kidney organs come from a donor with a kidney donor profile index of ≤0.35. The kidneys from these donors could otherwise be allocated to pediatric recipients, young adults or prior organ donors. This paper presents the new OPTN and United Network of Organ Sharing simultaneous liver–kidney allocation policy, provides the supporting evidence and explains the rationale on which the policy was based. Abstract : Simultaneous liver–kidney transplantation occurs without any standardized medical eligibility criteria, and the authors present a policy, developed by a committee representing a diverse group of transplant professionals, intended to bring order to this otherwise chaotic system.